Design and performance analysis of IoT-based portable waste incinerator for environmental efficiency and marketing - Immawan, Taufiq; Rofif , Muhammad Iqbal; Cahyo , Winda Nur; Waskita , Farid Agung; Suryoputro , Muhammad Ragil (OPSI, 2025)
The increasing volume of waste in urban areas such as Yogyakarta is not supported by adequate public awareness or effective waste management systems. This study aims to design and evaluate the performance of an IoT-based portable waste incinerator as an efficient and feasible solution for household and community use. The prototype was developed using an iterative design approach with recycled materials and low-cost IoT components. Test results show that the device maintains a stable combustion temperature of 600–800 °C and achieves an average waste volume reduction of 85%. SO₂ emission levels remain below 120 ppm, meeting environmental safety standards. The IoT monitoring system, using an ESP8266 module and DHT22 sensor, enables real-time tracking of temperature and ash accumulation and provides automatic alerts for maintenance. Financial analysis indicates that production costs can be reduced by approximately 40%, resulting in an estimated unit price below IDR 4,000,000. Market validation across five locations in Yogyakarta shows an 85% interest rate and a satisfaction score of 4.2/5. Overall, the IoT-based portable waste incinerator demonstrates technical reliability, environmental efficiency, and market viability.